Influence of sea surface temperature in the tropics on the Antarctic sea ice under global warming - G. V. Alekseev; N. I. Glok; A. E. Vyasilova; N. E. Ivanov; N. E. Kharlanenkova; A. V. Smirnov (Лëд и снег)
Sea ice fields in the Antarctic, in contrast to the Arctic ones, did not show a reduction in observed global warming, whereas the global climate models indicate its certain decrease. The purpose of the study is to explain this climatic phenomenon on the basis of the idea of joint dynamics of oceanic structures in the Southern Ocean – the Antarctic polar front and the margin of the maximum distribution of sea ice. We used data from the ERA/Interim and HadISST as well as the database on the sea ice for 1979–2017. Relationship between the SST-anomalies in low latitudes of the Northern hemisphere and positions of the Antarctic polar front and maximum sea-ice extent was investigated. It was found that locations of these structures changed under the influence of the SST anomalies in low latitudes. The results obtained confirm existence of the opposite trends in changes in the sea ice extent in the Arctic and Antarctic under the influence of the SST anomalies in the central North Atlantic Ocean. When positive, the anomalies cause a shift of the Intertropical Convergence Zone (ITCZ) and the Hadley circulation to the North, while, on the contrary, the negative anomaly promotes the corresponding shift of the Antarctic polar front, followed by the boundary of sea ice.